Lead isotopes in the Central Yellow Sea Mud: Evidence of atmospheric deposition and its implication for regional energy consumption shift. (1st January 2021) - Wu, Bin; Wu, Xiaodan; Shi, Xuefa; Zhang, Xuelei; Qiao, Shuqing; Hu, Limin; Liu, Jihua; Liu, Shengfa; Zhang, Jun; Zhang, Hui; Zhu, Aimei
Abstract: Anthropogenic activities have increased lead (Pb) emissions and impacted their spatiotemporal distributions in coastal seas. To quantify the increasing variability of Pb and identify the specific origins and their corresponding magnitudes, Pb and Pb isotopes are investigated in a well-placed sediment core covering the period of 1928–2008 in the Central Yellow Sea Mud (CYSM). The concentration of Pb varied from 27.17 μg/g to 37.30 μg/g upwardly along the core, with pronounced anthropogenic disturbance since the late 1960s. The Pb input history of the CYSM experienced five stages according to industrialization levels and Pb contamination, with relative pristine stages from 1928 to 1969 and human activity-impacted stages from 1969 to 2008. The 206 Pb/ 207 Pb ratio demonstrated an overall decreasing profile while the 208 Pb/ 206 Pb ratio displayed the reverse trend upwardly along the core, possibly due to the atmospheric delivery of anthropogenic Pb emissions from northern China. Furthermore, 208 Pb/ 206 Pb vs. 206 Pb/ 207 Pb shows certain linearity between natural sediment sources and anthropogenic emissions of Pb (atmospheric deposition); thus, atmospheric inputs account for 34–43% of the Pb in the sediment since Pb enrichment using the two-endmember mixing model. Moreover, the steep decrease in 206 Pb/ 207 Pb and rapid increase in 208 Pb/ 206 Pb since the 1970s suggest the introduction of leaded gasoline and the increasing proportionate consumption of gasoline relative to total energy consumption. The continuously decreasing 206 Pb/ 207 Pb ratio and increasing 208 Pb/ 206 Pb ratio since 2000 are the combined results of coal consumption, nonferrous smelting, and residual Pb contamination from leaded gasoline, which is quite distinctive from cases in North America and Europe. The relatively high 206 Pb/ 207 Pb and low 208 Pb/ 206 Pb ratios before 1969 represent the natural Pb isotopic signatures. Hence, Pb input is significantly affected by regional energy consumption and restructuring, and the Pb isotopic ratios may be a potential proxy for the shift in energy consumption. Graphical abstract: Image 1 Highlights: Five stages of Pb input are divided in the CYSM during 1928–2008. Aeolian Pb from China's fossil fuel combustion leads to Pb enrichment in the CYSM. Atmospheric deposition accounts for 34–43% of the Pb in the CYSM since late 1960s. Energy consumption and restructuring impact the Pb isotopic ratios. Pb isotopic ratios may be a potential proxy for the shift of energy consumption. Abstract : Pb isotopic ratios in the Central Yellow Sea Mud preserve the footprint of land energy activities and can be used as a potential proxy for the shift in energy consumption.